On the plastic surgery of the ears and nose: the Nepalese recension of the Suśrutasaṃhitā - Wujastyk, Dominik ca. 20./21. Jh. (Heidelberg Asian Studies Publishing, 2023)
A thousand-year-old Ayurvedic manuscript containing the Compendium of Suśruta was announced to the scholarly world in 2007. The Nepalese manuscript, since adopted by UNESCO as part of the Memory of the World, reveals the state of classical Indian medicine in the ninth century. It enables us to study the changes in this medical classic that have taken place from the ninth to the nineteenth century, when printed texts began to dominate the dissemination of the work. The present monograph describes the research project focussed on this manuscript and offers an edition, study and translation of the historically important chapter about the plastic surgery on the nose and ears.